2006
DOI: 10.1002/gcc.20342
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence ofBRCA1 genomic rearrangements in a large cohort of Italian breast and breast/ovarian cancer families without detectableBRCA1 andBRCA2 point mutations

Abstract: The presence of genomic rearrangements of the BRCA1 gene in breast and/or ovarian cancer families has been intensively investigated in patients from various countries over the last years. A number of different rearrangements have been reported by several studies that clearly document the involvement of this mutation type in genetic predisposition to breast and ovarian cancer. Population-specific studies are now needed to evaluate the prevalence of genomic rearrangements before deciding whether to include ad ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
40
1
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 24 publications
5
40
1
3
Order By: Relevance
“…Adding the three BRCA1 del (ex 9-12) mutations found among the sequence negative cases brings the overall prevalence of BRCA mutations in the cohort to 34% (37 of 110)-the large rearrangement representing 8.8% (3 of 37) of all BRCA carriers. This proportion of rearrangements among BRCA1-positive individuals is consistent with previous studies in European and American populations (3,4,6,(28)(29)(30)(31).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Adding the three BRCA1 del (ex 9-12) mutations found among the sequence negative cases brings the overall prevalence of BRCA mutations in the cohort to 34% (37 of 110)-the large rearrangement representing 8.8% (3 of 37) of all BRCA carriers. This proportion of rearrangements among BRCA1-positive individuals is consistent with previous studies in European and American populations (3,4,6,(28)(29)(30)(31).…”
Section: Discussionsupporting
confidence: 92%
“…Five of eight BRCA1 rearrangements (five deletions, two duplications, and one amplification) identified in this cohort were novel; one has been reported to be a French founder mutation (deletion of exons 8-13; ref. 32) and two others (deletion of exons 11-15 and duplication of exon 20) were also reported in Portuguese (31) and Italian cohorts (28). However, the BRCA1 del (9-12) mutation has not been reported in any other study population to date.…”
Section: Discussionmentioning
confidence: 83%
“…This rate is somewhat higher than those previously recorded in other populations such as in Spain (8.2%) [19], Germany (9.6%) [20], France (12.0%) [5], Czech Republic (12.3%) [21] and Denmark (12.5%) [22], but is lower than that recorded in the Netherlands (27.3%) [13]. Our reported percentage is in agreement with the results of Agata et al in Italy, who reported about 19% of LGRs in a large cohort of breast and breast/ovarian cancer families without BRCA1 and BRCA2 point mutations detectable by conventional scanning methods [14].…”
Section: Discussionsupporting
confidence: 82%
“…Indeed, the incidence of BRCA1 LGRs in patients with strong family history of breast cancer ranges from 0.8%-23%, which represents around 8%-40% contribution to the BRCA1 mutation spectrum in different ethnic groups [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Pathogenic alterations in BRCA1 include mutations in the regulatory regions of the gene, splice site mutations, nonsense/ frameshift/missense mutations, and large chromosomal rearrangements, estimated to account for ~19% of all BRCA1 mutations in Italian patients (13).…”
Section: Introductionmentioning
confidence: 99%